Reading and understanding : an introduction to the psychology of reading - Underwood, Geoffrey (Blackwell, 1996)
Reading as skilled information processing. Cognotive processes in word recognition. Reading development and reading difficulties. Neuropsychological studies of reading. The role of eye movements in reading. Reading comprehension.